2011
DOI: 10.1007/s11244-011-9689-7
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation of a Ni-Based Reforming Catalyst During the Upgrading of the Producer Gas, from Simulated to Real Conditions

Abstract: The deactivation of a nickel reforming catalyst during the upgrading of the producer gas obtained by gasification of lignocellulosic biomass was studied. The research involved several steps: the selective deactivation of the catalyst in a laboratory scale; the streaming of the catalyst with the producer gas of a downdraft and an oxygen/steam circulating fluidized bed (CFB) gasifier; and tests in a reformer placed in a slipstream of the CFB gasifier. The information obtained allowed to elucidate the catalyst de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Many alternatives are available and have been the focus of much research, such as steam reforming, (SR), autothermal reforming, (ATR) and catalytic partial oxidation, (CPO). The main problem with the mentioned techniques is that they rely on catalysts which are highly susceptible to sulfur poisoning [11][12][13][14]. Although much research has been devoted to finding suitable catalysts for this area no clear alternative has yet emerged.…”
Section: Introductionmentioning
confidence: 99%
“…Many alternatives are available and have been the focus of much research, such as steam reforming, (SR), autothermal reforming, (ATR) and catalytic partial oxidation, (CPO). The main problem with the mentioned techniques is that they rely on catalysts which are highly susceptible to sulfur poisoning [11][12][13][14]. Although much research has been devoted to finding suitable catalysts for this area no clear alternative has yet emerged.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray photoelectron spectroscopy (XPS) also indicated that Ni 0 peak was shifted to higher values (853.4 eV from 852.5 eV) which was ascribed to the different chemical environment of Ni 0 from the presence of Ni7S6. Ni (211), determined that both surfaces are prone to sulfidation due to the low energy barrier [114]. The studied reaction products (i.e.…”
Section: Catalytic Tar Reforming Processesmentioning
confidence: 99%
“…As detailed in Chapter 2, the effectiveness of Ni catalysts has also been limited as they can be easily deactivated due to the presence of impurities. Sulfur compounds such as H2S and COS, and halide compounds such as HCl represent some of the syngas impurities that have a detrimental effect on Ni catalyst performance, poisoning reforming as well as water-gas shift (WGS) activities of Ni-based catalysts [31,32,92,131,143,144,211,212]. Halogen species, such as HCl, chemisorbs onto the active Ni sites forming NiX2 complexes (X = halogen).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations